A thermal optimization throughan innovative mechanism of free convection flow of Jeffrey fluid using non-local kernel. (April 2021) - Awan, Aziz Ullah; Ali, Qasim; Riaz, Samia; Shah, Nehad Ali; Chung, Jae Dong
Abstract: Optimality for operating temperature can improve the reliability of thermodynamics of convection flow of Jeffrey fluid through mathematical techniques; this is because thermal convection is invoked in several engineering problems for knowingan accurate assessment and stable or unstable heat transference characteristics. In this context, the free convection flow of Jeffrey fluid among two vertical plates is characterized by stable or unstable heat transfer. The heat transference mechanism is designed by employing a generalized and a fractional form of Fourier's law that delivers damping for thermal flux. In this process, we make use of the Caputo time-fractional derivative (CTFD) having a power-law singular kernel. The free convection is induced by the temperature gradient. The analytical solutions have been obtained through a method of Laplace coupled with finite sine-Fourier transform and have been embedded with regards to the Mittag-Leffler function. The behavior of velocity and temperature profiles is analyzed through numerical computations and graphical representations for different embedded parameters with Mathcad. Certainly, this article presents a comprehensive discussion as well as a graphical interpretation of the achieved results.